2005
DOI: 10.1021/cm0504440
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Synthesis of Inorganic Nanospheres

Abstract: The synthesis of silica, silver bromide, and composite nanospheres made in the presence of block copolypeptide vesicles is reported. Hollow silica nanospheres of controllable size can be made with Lys:Phe 1:1 block copolypeptides, whereas at higher block ratios, uniform silica nanospheres are formed that are not hollow. Silver bromide nanospheres of controllable size in the range of 25−250 nm can also be formed, as well as silver bromide/silica core−shell particles. The silver bromide nanospheres can also be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 59 publications
(93 reference statements)
3
81
0
Order By: Relevance
“…[25] The latter point is consistent with previous work from our lab. [29] Also consistent with previous work is that the Lys- ) are absent. Figure 1 shows the FE-SEM images of silicas formed in the presence of Lys 340 -b-Gly 85 and Lys 320 -b-Gly 160 for each of the three synthesis methods.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…[25] The latter point is consistent with previous work from our lab. [29] Also consistent with previous work is that the Lys- ) are absent. Figure 1 shows the FE-SEM images of silicas formed in the presence of Lys 340 -b-Gly 85 and Lys 320 -b-Gly 160 for each of the three synthesis methods.…”
supporting
confidence: 91%
“…This was observed in our previous work with Lys-Phe polymers possessing high Lys:Phe ratios. [29] In the case of the most kinetically trapped vesicles we have made to date (1:1 Phe-Lys polymers) the vesicles were so robust that hollow spheres were formed. These are not observed for any of the syntheses reported here.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Polymer Vesicles -Polymer Crosslinking [124] -Polymeric Micelles [125] Lipid Vesicles -Nanosized Liposome [126] Charged Polypeptide -Peptide Crosslinking [127] Inorganic Vesicles -Inorganic Synthesis [128] Receptor T/B Cell ReceptorNK Cell ReceptorImmune Signaling ComplexNeurotransmitter ReceptorIntegrin…”
Section: Typementioning
confidence: 99%
“…Diatom cells are beautifully elaborate silica shells that have nanoscale hooks, holes and gorges that are believed to be formed by a fibrous protein core [64,65]. Indeed, it has been previously shown that fibrous proteins can mediate templating of tetraethyl orthosilicate to form silica [66 - and that arginine and lysine play an important role in the templating process [67][68][69]. In recent work, we used the library of variants of the sequence 'KFFEAAAKKFFE' to explore whether these fibrils can form silica wires and how the sequence contributes to the morphology of the resulting structures.…”
Section: Decorating the Exterior Of Amyloid Fibrilsmentioning
confidence: 99%